Event-related EEG responses to anticipation and delivery of monetary and social reward. - Flores, Amanda; Münte, Thomas; Doñamayor, Nuria (My University, 2015)
Monetary and a social incentive delay tasks were used to characterize reward anticipation and delivery with electroencephalography. During reward anticipation, N1, P2 and P3 components were modulated by both prospective reward value and incentive type (monetary or social), suggesting distinctive allocation of attentional and motivational resources depending not only on whether rewards or non-rewards were cued, but also on the monetary and social nature of the prospective outcomes. In the delivery phase, P2, FRN and P3 components were also modulated by levels of reward value and incentive type, illustrating how distinctive affective and cognitive processes were attached to the different outcomes. Our findings imply that neural processing of both reward anticipation and delivery can be specific to incentive type, which might have implications for basic as well as translational research. These results are discussed in the light of previous electrophysiological and neuroimaging work using similar tasks.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/15493
Keywords: Reflejos condicionados; Motivación; Monetary incentive delay,; Social incentive delay; Electroencephalography; Reward anticipation